IMPLEMENTING VARIOUS MIXED METHODS TO DEVELOP COMMUNICATIVE SKILLS. (Ta'limning zamonaviy transformatsiyasi, 2025)
Annotation: This article explores the application of mixed methods in developing communicative skills across diverse contexts. It integrates theoretical foundations, empirical findings, and practical applications to illustrate how a combination of quantitative and qualitative approaches enhances language learning outcomes. The paper emphasizes the significance of interactive strategies, multimodal tools, and learner-centered methodologies.